PARTISIPASI MASYARAKAT DALAM PEMILU SERENTAK TAHUN 2019 DI KABUPATEN BULELENG - KAMAJAYA, GEDE (Jurnal Ilmiah Widya Sosiopolitika, 2021)
BSTRACT The 2019 election is the first simultaneous election in Indonesia. In addition to electing the president and vice president, the 2019 election also elects members of the DPR RI, DPD, Provincial DPR, and City Regency DPRD. The 2019 simultaneous elections were implemented after previously there was a lawsuit against Law No. 42 of 2008. One of the most important things in a democratic climate is public participation in the policy-making process and political process. One form of public participation in the policy-making process and political process is the involvement of citizens in the election process. This study aims to determine the extent of the participation of the Buleleng people in the 2019 simultaneous elections. To obtain the results to be achieved as mentioned above, this study uses a qualitative method by collecting data from interviews to document studies. The results of this study indicate that the number of users of the right to vote in Buleleng Regency is 439,787 people. In percentage terms, public participation in simultaneous elections in Buleleng Regency is 73.91%. In the 2019 simultaneous elections, there were 596,589 voters in Buleleng. Meanwhile, the number of voting rights users reached 439,787 people who were divided into 2,146 polling stations. The high participation rate is due to the success of KPU socialization, massive information in the media. Of all the regencies in Bali, Buleleng was recorded as one of the districts with a fairly high invalid vote rate of 37,449 while the number of valid votes was 401,818. The high number of invalid votes is due to technical difficulties, especially for the elderly. In Buleleng Regency itself, the elderly voter rate is the highest compared to other districts and cities with a total of 92,101 with the number of male voters is 42,170 and the number of female voters is 49,931. Keywords : Buleleng Regency, Public Participation, Election, Political Communication